Bottle sample data collected every 4 hours at 0 and 100 cm depth - Mariana Ribas-Ribas; Ander López-Puertas; Oliver Wurl; Sanja Frka (PANGAEA, 2025)
Discrete samples collected every 4 hours from the SML and ULW used to calculate the carbon System parameters with CO2Sys.
In: Ribas-Ribas, M et al. (2025): Diel variability of thermohaline and carbon system parameters in the sea-surface microlayer and underlying water of a Mediterranean coastal site (Šibenik, Croatia) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984017